Multiple Congenital Segmental Dilatations of Colon: A Case Report - Bilal Mirza; Nabi Bux (EL-Med-Pub, 2012)
Congenital segmental dilatation of colon (CSDC) is a rare malformation in neonates. A single segmental dilatation of colon is mentioned in the available case reports. Not a single case of multiple CSDC is reported hitherto. We report a case of multiple CSDC associated with cleft lip and palate, and rectal atresia.